An experimental and numerical study of moisture transport and moisture-induced strain in fast-grown sitka spruce - O’Ceallaigh, Conan; Sikora, Karol; McPolin, Daniel; M. Harte, Annette (Maderas. Ciencia y Tecnología, 2019)
The use of fast-grown timber in the manufacture of engineered wood products is increasing; however, the fast growth rate results in a low-density timber that is susceptible to significant swelling and shrinkage deformations under changing moisture content. The current study focuses on the characterisation of the moisture diffusion and swelling/shrinkage of fast-grown Sitka spruce and the prediction of the moisture-induced strain development in Sitka spruce glulam beams under variable humidity cycles. Moisture content evolution and swelling/shrinkage coefficients were measured and the longitudinal swelling/shrinkage was found to be significantly greater than for slow-grown timber. Sitka spruce glued-laminated beams were subjected to controlled relative humidity cycling for 52 weeks and the moisture distribution and moisture-induced strains were measured continuously. Coupled moisture-displacement numerical models, incorporating the experimentally measured material parameters were developed. The effect of the glue-line was found to have an insignificant effect on moisture transport, however, the material orientation greatly influenced the predicted moisture-induced strain. Accurately mapping the material orientation produced significantly better predictions of the experimental results over the 52-week period.